Pengaruh Struktur Aset, Profitabilitas, Biaya Agensi, Inovasi dan Teknologi, Ukuran Perusahaan terhadap Struktur Modal : Bukti Dari Sektor Teknologi Indonesia. - Silvia Caroline; Ickhsanto Wahyudi (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This study aims to determine the determinants of a company's capital structure (debt ratio) such as asset structure, profitability, agency costs, innovation and technology, and company size. The population in this study uses technology companies and are listed on the Indonesia Stock Exchange in the period 2019 – 2021 using a purposive sampling method that meets the research criteria with panel data analysis. The determination of the research sample was based on a purposive sampling method with a total sample of 36.The data used is secondary data derived from the company's financial reports which have been accessed via www.idx.co.id. Secondary data processing using eviews analysis techniques. The results of this study indicate that asset structure has a positive influence on capital structure; however, profitability, agency costs, innovation and technology, and company size do not affect the capital structure. For Technology Companies listed on the IDX, based on the results of this research, it is hoped that they can provide broad insight to company management to oversee the company's capital structure in a good, effective and efficient manner, thus enabling companies to take advantage of the capital structure. For investors and potential investors, if they want to invest, it is advisable to look at the financial condition of the company which can describe the company's value every year in the form of annual income and dividends distributed by the company and consider the company's cash flow before making a decision to invest in a technology sector company listed on IDX so that investors can provide capital to the right companies and have good value